CAD of Ion Mirror as an Aberration Corrector - Waheeb, Hussain A; Abass, Hala F (Al-Nahrain Journal of Science, 2017)
The present work have has been focused on suggesting a mathematical form of an axial potential distribution for an ion mirror. The equation that has been found gave us the best value of the mirror function. The Bimurzaev techniques had been investigated to find mirror trajectory using Runge-Kutta method. The profiles of the mirror that had been applied under Bimurzaev techniques lead us to conclude that the mirror has two electrodes. The coefficients of spherical and chromatic aberrations of the mirror have been computed and normalized in terms of the focal length. The choice of the mirror depends on the operational requirements, i.e. whether it is intended operate the electrostatic mirror in an optical system at low spherical aberration mode or at low chromatic aberration mode.